PENGEMBANGAN LEMBAR KEGIATAN SISWA BERORIENTASI CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI FOTOSINTESIS KELAS VIII SMP - AYU KRISNAWATI, SYLVIA AYU (PENSA E-JURNAL: PENDIDIKAN SAINS, 2013)
Abstrak Penelitian ini bertujuan untuk mengetahui kelayakan, dan respon siswa terhadap LKS berorientasi CTL pada Materi Fotosintesis di kelas VIII SMP yang dikembangkan. Penelitian ini merupakan penelitian pengembangan LKS dengan sasaran penelitian berupa LKS berorientasi CTL pada Materi Fotosintesis. Sumber data dalam penelitian ini adalah tim ahli meliputi dosen dan guru IPA penelaah dan validator, serta 15 siswa kelas VIII SMP. Rancangan penelitian ini mengacu pada model pengembangan media oleh Peter Fenrich. Pengumpulan data dilakukan menggunakan lembar angket validasi dan respon siswa, sedangkan instrumen penelitian yang digunakan berupa lembar telaah, lembar validasi, dan lembar angket respon siswa. Analisis data dilakukan secara deskriptif kualitatif untuk hasil telaah dan deskriptif kuantiatif dari persentase hasil validasi, dan respon siswa untuk mengetahui kelayakan LKS berorientasi CTL yang dikembangkan. Hasil penelitian menunjukkan bahwa LKS berorientasi CTL yang dikembangkan telah layak digunakan dalam proses pembelajaran untuk SMP karena telah memenuhi kelayakan berdasarkan kriteria kesesuaian terhadap 4 komponen CTL, kelayakan isi, dan penyajian masing-masing dengan persentase berturut-turut sebesar 91,67%; 95%; 93,75%. Selain itu adanya respon positif siswa terhadap LKS yang ditunjukkan dengan respon tentang kelayakan berdasarkan 4 komponen CTL, kelayakan Isi dan penyajian berturut-turut sebesar 95,24%; 96,67%; 95,55%. Kata Kunci: LKS, CTL, Fotosintesis. Abstract This research was conducted to know the feasibility of Student Activity and also the students response toward Student Activity with CTL Orientation in the Photosynthesis Topic for Grade VIII of Junior High School which developed. This research is targeting the development of LKS research is oriented to Content Photosynthesis CTL. Sources of data in this research is a team of experts covering a lecturer and Science teacher reviewers and validators, and 15 eighth grade students of SMP. The design of this study refers to the model of the development of media by Peter Fenrich. The data was collected using a questionnaire sheet validation, and student response sheets questionnaire, while the instruments used in this research study in the form of sheet, sheets validation, and student response sheets questionnaire. Descriptive data were analyzed qualitatively for the review and descriptive kuantiatif percentage of validation results and student responses to determine the feasibility of CTL-oriented Student Activity are developed This research is kind of development research with the target research is Student Activity with CTL Orientation in the Photosynthesis Topic which developed. The data sources of this research resulted by expert team consist of lecture and teacher of science as reviewer and validator, and 15 student of Junior High School in grade VIII. The research design refer to Media Development Model by Peter Fenrich. The data was collected using a questionnaire sheet, while the research instrument using review sheet, validation sheet, and questionnaire of student response. A method of data analysis was done by descriptively qualitative for analysis the result of Student Activity review and descriptive quantitative of percentages of assessment result and student response. The results showed that Student Activity with CTL Orientation in the Photosynthesis Topic which have been developed, competent used in the learning process for grade VIII of Junior High School, since has met feasibility criteria for suitability with four component of CTL, Criteria of Content, and Presentation which respectively for 91,67%; 95%; 93,75%. In addition the students' positive responses to the student worksheets as indicated by the response of eligibility based on four components of CTL, feasibility, and presentation of content, respectively for 95.24%, 96.67%, 95.55%. Keywords: Student Activity, CTL, photosyntesis.